METHODOLOGY OF TEACHING THE UZBEK LANGUAGE IN RUSSIAN GROUPS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
Uzbekistan's linguistic landscape is shaped by the political and historical events of the 20th century. While Uzbek is the dominant native language, spoken by roughly 80% of the population (mostly ethnic Uzbeks), the remaining 20% speak dozens of other languages. Russian is a prominent native language for a significant portion of the population and frequently serves as a second, third, or foreign language for many nonRussian speakers. The status of both Uzbek and Russian has evolved significantly throughout the 20th and 21st centuries.